2016
DOI: 10.3389/fenvs.2016.00071
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of the Aquatic Environment with Neonicotinoids and its Implication for Ecosystems

Abstract: The widespread use of systemic neonicotinoid insecticides in agriculture results first in contamination of the soil of the treated crops, and secondly in the transfer of residues to the aquatic environment. The high toxicity of these insecticides to aquatic insects and other arthropods has been recognized, but there is little awareness of the impacts these chemicals have on aquatic environments and the ecosystem at large. Recent monitoring studies in several countries, however, have revealed a worldwide contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(119 citation statements)
references
References 105 publications
2
110
1
6
Order By: Relevance
“…Regarding neonicotinoids, the most recent review of surveys in 11 countries found the frequency of detections between 13% (acetamiprid) and 57% (dinotefuran) of their surface waters and current residue levels ranging from an average 80 ng/L (dinotefuran) to 730 μg/L (imidacloprid). Both frequency and residue levels showed increasing trends over the past 10 years, in agreement with their increasing use as pest control products all over the word (Sánchez-Bayo et al 2016a).…”
Section: Water and Sedimentssupporting
confidence: 67%
“…Regarding neonicotinoids, the most recent review of surveys in 11 countries found the frequency of detections between 13% (acetamiprid) and 57% (dinotefuran) of their surface waters and current residue levels ranging from an average 80 ng/L (dinotefuran) to 730 μg/L (imidacloprid). Both frequency and residue levels showed increasing trends over the past 10 years, in agreement with their increasing use as pest control products all over the word (Sánchez-Bayo et al 2016a).…”
Section: Water and Sedimentssupporting
confidence: 67%
“…Risks to other organisms have also been identified . More recent in vitro, in vivo, and ecological field studies indicate that neonicotinoids can have adverse effects on vertebrate and invertebrate species, as well as mammals .…”
Section: Characteristics Of the Pesticides From The Eu First And Secomentioning
confidence: 99%
“…[22,46] Risks to other organisms have also been identified. [47][48][49] More recent in vitro, in vivo, and ecological field studies indicate that neonicotinoids can have adverse effects on vertebrate and invertebrate species, as well as mammals. [50] In addition, certain neonicotinoid metabolites have been found to be as or more toxic than the parent compound.…”
mentioning
confidence: 99%
“…If not available in the risk assessment, exposure in connected off-site ecosystems can be considered based on generic assumptions, for example, we consider an agricultural field of 250 m  250 m with a ditch on 2 sides having the standard 30 cm depth  2 m width and 250 m length (details given in Supplemental Data II). Most of the applied (80-97%) neonicotinoids from coated seeds end up in the soil and porewater (Goulson et al [16] and Sanchez-Bayo [14]), and leach into the groundwater and adjacent drainage ditches. In the most positive scenario, which uses a relatively fast degradation time (half-life ¼ 27 d) and 10 d of leaching before reaching the adjacent ditch system, concentrations in the ditches are approximately 38.7 mg/L.…”
Section: Toward Postregistration Assessment In Policy and Managementmentioning
confidence: 99%